Mengembangkan Kemampuan Intelektual Dan Kepekaan Sosial Anak SDK St. Yoseph Kuaputu Melalui Aplikasi Pembelajaran Kooperatif Jigsaw - Soterdino D. Obe; Hermalindo Meomanu; Armandino A. Da Costa; Siprianus S. Senda (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Education is a systematic and programmed effort to develop all aspects of human life so that they become mature and balanced. Therefore the development of various actual and adequate educational methods is needed to support human development. Among the various methods that have been successfully developed, the Jigsaw Cooperative Learning Method is one that is very well practiced in today's learning environment. The jigsaw cooperative learning method aims to develop intellectual abilities and train students' social sensitivity. Realizing this use, the author carries out community service activities in the form of the Jigsaw Cooperative Learning application at Santo Yoseph Kuaputu Catholic Elementary School, which aims to develop the intellectual aspects and social sensitivity of students. The result achieved is the growth of intellectual capacity and social sensitivity in interactions in the classroom and in the local social environment.